Sistem Monitoring Berbasis IoT untuk Deteksi Intrusi Air dan Kendali Pompa Otomatis pada Perahu Nelayan - Hasiri, Ery Muchyar; Suryawan, Mohamad Arif; Musriddin, Musriddin (Informatics Engineering Department, Dayanu Ikhsanuddin University, 2025)
The high risk of water leakage in fishing boats remains a significant safety concern, particularly when fishermen operate under high waves or heavy rainfall. Accumulated water inside the hull often goes undetected because inspection and drainage processes are still performed manually, resulting in slow response, reduced vessel safety, and a higher potential for sinking. These conditions highlight the need for an automated monitoring mechanism capable of providing real-time information remotely. This study aims to design a prototype monitoring system for fishing boats that can detect water height inside the hull and automatically activate a drainage mechanism based on the Internet of Things (IoT) using an ESP32 microcontroller. The research method includes field observation, interviews, literature studies, hardware and software design, and functional testing of the ADS1115 sensor, water pump, and data transmission via Wi-Fi communication. The system is built using ESP32, ADS1115, a water pump, relay, solar panel as power supply, and an Android-based application for remote monitoring. Experimental results show that the sensor provides stable water-level measurements, the pump activates automatically when the water exceeds the 25% threshold, and monitoring data are transmitted quickly and accurately. The system is considered effective in improving safety and operational efficiency for fishermen in managing water accumulation inside fishing boats.